2019
DOI: 10.3390/plants8090295
|View full text |Cite
|
Sign up to set email alerts
|

Assisting Phytoremediation of Heavy Metals Using Chemical Amendments

Abstract: Phytoremediation is one of the safer, economical, and environment-friendly techniques in which plants are used to recover polluted soils, particularly those containing toxic organic substances and heavy metals. However, it is considered as a slow form of remediation, as plants take time to grow and flourish. Various amendments, including the augmentation of certain chemical substances i.e., ethylenediamine tetraacetic acid (EDTA), ethylene glycol tetra acetic acid (EGTA), and sodium dodecyl sulfate (SDS) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 95 publications
(114 reference statements)
0
60
0
Order By: Relevance
“…Several investigations have been carried out on EDTA as a heavy metals chelator from polluted water and soils for effective phytoextraction [204,206,207]. In several studies, it has been reported that the application of EDTA in contaminated soils leads to elevated Cd accumulation in the aerial parts of plants [207,208].…”
Section: Chelate-assisted Cadmium Phytoremediationmentioning
confidence: 99%
“…Several investigations have been carried out on EDTA as a heavy metals chelator from polluted water and soils for effective phytoextraction [204,206,207]. In several studies, it has been reported that the application of EDTA in contaminated soils leads to elevated Cd accumulation in the aerial parts of plants [207,208].…”
Section: Chelate-assisted Cadmium Phytoremediationmentioning
confidence: 99%
“…It has been demonstrated that in superior plants, different phytoremediation routes are presented, although the time used to phytoremediate polluted soils normally becomes longer due to the slow growth of most of the species [122]; these aspects need to be dealt with to convert this environmental biotechnology into a more attractive and affordable option. Studies are being implemented to turn this drawback into opportunities; for example, Pilipović et al [123] reported long-term poplar phytoremediation in which biomass productivity and carbon storage during a rotation of Populus deltoides Bartr.…”
Section: Liquid Biofuelsmentioning
confidence: 99%
“…Soil is the main source of contamination, where from heavy metals can move to the surface of the roots by diffusion or ion exchange between the surface of the root and soil-water. Plants use active absorption to assimilate essential metals, but they can also take up other toxic elements available in the soil (Figure 1) [51]. At the same time, heavy metals can move through cationic channels in the cell membrane inside the cell [16,52,53].…”
Section: Interactions Between Soil Heavy Metals and Medicinal Plantsmentioning
confidence: 99%
“…Sources of heavy metals, and foliar, root uptake of heavy metals in plants (from Hasan et al[51], according to the provisions MDPI "This is an open access article distributed under the Creative Commons Attribution License which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited") Metals-plants interactions during metal transport from polluted medium to plant https://doi.org/10.37358/RC.20.7.8222…”
mentioning
confidence: 99%